2013
DOI: 10.1177/0044118x13491581
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Meso-System

Abstract: Community contexts are important ecological settings related to problem behavior and positive youth development (PYD). While substantial work has focused on neighborhood disadvantage, the current study explores the role of community assets, specifically linkages to important institutional resources and people in those settings. These concepts are explored in a crosssectional sample of African American and White, male and female adolescent offenders with an eye toward approaches to reducing further delinquency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 59 publications
0
3
0
1
Order By: Relevance
“…En este sentido, son numerosos los autores que señalan que estas variables se relacionan con el ajuste psicosocial (Albanesi, Cicognani y Zani, 2006;Alfaro, Guzmán, Sirlopú, Oyarzún, Reyes, Benavente y de Rota, 2017;Herrero y Gracia, 2004;Hull et al, 2008;Vieno, Nation, Perkins y Santinello, 2007). Asimismo, se ha constatado que la implicación y la participación comunitarias tienen un efecto amortiguador en los adolescentes respecto de los efectos negativos del estrés (Dumont y Provost, 1999;Smith, Faulk y Sizer, 2016) y de la implicación en conductas violentas en la escuela (Jiménez, Musitu, Ramos y Murgui, 2009;Moreno, Povedano y Estévez, 2010). Se ha observado que el hecho de sentirse implicado en la comunidad y de participar en ella potencia la sensación individual de competencia, el autoconcepto, la autoestima, la autoeficacia y el autocontrol, lo que contribuye, a su vez, a un mayor bienestar y ajuste personal y social en los adolescentes (Palomar y Lanzagorta, 2005;Rey, Extremera y Pena, 2011;Smetana, Campione-Barr y Metzger, 2006;Vieno et al, 2007).…”
unclassified
“…En este sentido, son numerosos los autores que señalan que estas variables se relacionan con el ajuste psicosocial (Albanesi, Cicognani y Zani, 2006;Alfaro, Guzmán, Sirlopú, Oyarzún, Reyes, Benavente y de Rota, 2017;Herrero y Gracia, 2004;Hull et al, 2008;Vieno, Nation, Perkins y Santinello, 2007). Asimismo, se ha constatado que la implicación y la participación comunitarias tienen un efecto amortiguador en los adolescentes respecto de los efectos negativos del estrés (Dumont y Provost, 1999;Smith, Faulk y Sizer, 2016) y de la implicación en conductas violentas en la escuela (Jiménez, Musitu, Ramos y Murgui, 2009;Moreno, Povedano y Estévez, 2010). Se ha observado que el hecho de sentirse implicado en la comunidad y de participar en ella potencia la sensación individual de competencia, el autoconcepto, la autoestima, la autoeficacia y el autocontrol, lo que contribuye, a su vez, a un mayor bienestar y ajuste personal y social en los adolescentes (Palomar y Lanzagorta, 2005;Rey, Extremera y Pena, 2011;Smetana, Campione-Barr y Metzger, 2006;Vieno et al, 2007).…”
unclassified
“…These lower levels in perceived familial support in sexual minority individuals have been found to be associated with increased emotional distress (Doty et al, 2010), depression, and substance use (Needham & Austin, 2010), as well as decreased self‐esteem (Ryan et al, 2010). Alternatively, researchers have found that higher levels of familial understanding have been found to be a resiliency factor for sexual minority individuals during the transition to adulthood (Kosciw et al, 2015; Ryan et al, 2010; Sheets & Mohr, 2009; Smith et al, 2016). For example, Ryan and colleagues (2010) found that a greater sense of parental acceptance of one's sexual minority status was associated with increases in self‐esteem during adolescence.…”
Section: Familial Influences On Self‐esteem Development For Sexual Mi...mentioning
confidence: 99%
“…Little's conception of PYD, as arising from nurturing, positive relations between the strengths of a young person and the resources in the context-for instance, prosocial peer relationships (e.g., Smith et al, 2016) and, perhaps particularly, warm, trusting, and nurturing relationships between a youth and a caring and competent adult (e.g., Rhodes, 2020)-was both a product and a producer of the historical moment. That is, his conception was formulated in a zeitgeist that included discussions of several other ideas pertinent to a strength-based approach to youth development.…”
Section: The Long Past and The Short History Of Interest In Pydmentioning
confidence: 99%